Fort Colville and Hudson's Bay Company, Colville Washington, 1888 - University of Washington Libraries
Several wooden buildings; at the far left is a blockhouse. Caption on image: Hudson Bay Co. Ft. Colvile, Washington. 1888. Showing stockade.